Odpowiedź:
[tex]a_1 = 675\\a_{22} = 675*q^{21}\\a_{23} = 675*q^{22}\\a_{21} = 675*1^{20}\\ \\675*q^{21} = \frac{5}{4} *675*q^{22} + \frac{1}{5} *675*q^{20}[/tex] / : ( 675*q[tex]^{20})[/tex]
q = 1,25 q² + 0,2
1,25 q² - q + 0,2 = 0 / * 4
5 q² - 4 q + 0,8 = 0
Δ = 16 - 4*5*0,8 = 16 - 16 = 0
q = [tex]\frac{4}{10} = \frac{2}{5}[/tex]
S = [tex]\frac{675}{1 - \frac{2}{5} }[/tex] = [tex]\frac{675}{\frac{3}{5} }[/tex] = 675* [tex]\frac{5}{3}[/tex] = [tex]\frac{3375}{3}[/tex] = 1 125 - suma ciągu geometrycznego
Mamy ponadto
[tex]a_3 = 675*q^2 = 675*\frac{4}{25} = 108[/tex]
czyli
[tex]b_4 = 108[/tex]
[tex]b_{25} = b_1 + 24 r = (b_1 + 3 r) + 21 r = b_4 + 21 r = 108 + 21 r\\[/tex]
S[tex]_{25} = 0,5*( b_1 + b_{25})*25 =[/tex] S = 1 125 / *2
([tex]b_1 + b_{25}[/tex] )*25 = 1 125*2 / : 25
b[tex]_1 + b_{25}[/tex] = 90
( 108 - 3 r ) + ( 108 + 21 r ) = 90
18 r + 216 = 90
18 r = - 126 / : 18
r = - 7
[tex]b_1 = b_4 - 3 r = 108 - 3*( -7) = 108 + 21 = 129[/tex]
Odp. [tex]b_1 = 129\\[/tex]
==============
Szczegółowe wyjaśnienie: